The origins of nationalism an alternative history from ancient Rome to early modern Germany - Hirschi, Caspar; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2012)
"In this wide-ranging work, Caspar Hirschi offers new perspectives on the origins of nationalism and the formation of European nations. Based on extensive study of written and visual sources dating from the ancient to the early modern period, the author re-integrates the history of pre-modern Europe into the study of nationalism, describing it as an unintended and unavoidable consequence of the legacy of Roman imperialism in the Middle Ages. Hirschi identifies the earliest nationalists among Renaissance humanists, exploring their public roles and ambitions to offer new insight into the history of political scholarship in Europe and arguing that their adoption of ancient role models produced massive contradictions between their self-image and political function. This book demonstrates that only through understanding the development of the politics, scholarship and art of pre-modern Europe can we fully grasp the global power of nationalism in a modern political context"--
Machine generated contents note: 1. Introduction; 2. The modernist paradigm: strengths and weaknesses; 3. Foundations of a new nationalism theory; 4. Killing and dying for love: the common fatherland; 5. Competing for honour: the making of nations in late medieval Europe; 6. The nationalist transformation of borders and languages; 7. Humanist nationalism; 8. A German Emperor for the German people; 9. Nation and denomination; 10. Conclusion.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nationalism -- History; Nationalism -- Europe -- History; Nationalism -- Philosophy; Electronic books